2000
DOI: 10.1021/jf990994g
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antioxidant Activity of Flavonoid Metabolites in Plasma and Urine of Eriocitrin-Treated Rats

Abstract: Eriocitrin, a flavonoid glycoside present in lemon fruit, is metabolized in vivo to a series of eriodictyol, methylated eriodictyol, 3,4-dihydroxyhydrocinnamic acid, and their conjugates. Plasma antioxidant activity increased following oral administration of aqueous eriocitrin solutions to rats. Eriocitrin metabolites were found in plasma and renal excreted urine through HPLC and LC-MS analyses. Eriocitrin was not detected in plasma and urine, but eriodictyol, homoeriodictyol, and hesperetin in their conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
90
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 27 publications
5
90
1
Order By: Relevance
“…Eriocitrin is converted to eriodictyol and 3,4-dihydroxyhydrocinnamic acid (3,4-DHCA) by intestinal bacteria, and conjugated forms of eriodictyol, homoeriodictyol and hesperetin, and free 3,4-DHCA were detected in rat plasma. 28 Shimoi et al 29 have suggested that deglucuronidation occurs at focal sites during inflammation. Thus eriodictyol in a free form possibly plays an important role in the inhibition of LOX activity during inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Eriocitrin is converted to eriodictyol and 3,4-dihydroxyhydrocinnamic acid (3,4-DHCA) by intestinal bacteria, and conjugated forms of eriodictyol, homoeriodictyol and hesperetin, and free 3,4-DHCA were detected in rat plasma. 28 Shimoi et al 29 have suggested that deglucuronidation occurs at focal sites during inflammation. Thus eriodictyol in a free form possibly plays an important role in the inhibition of LOX activity during inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the resistance effect of oxidation in whole plasma after ingestion of LA in rat has been reported (Miyake et al, 2000). The resistance effect of LDL oxidation in plasma has been associated with prevention of cardiovascular disease (Goldstein et al, 1979;Sies et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…LF, which is prepared from lemon peel and predominantly contains eriocitrin, has been reported to have low bioavailability when orally ingested by humans (Miyake et al, 2006b), although it exhibited bioactivities such as a suppressive effect on oxidative stress in experimental animals (Miyake et al, 1998(Miyake et al, , 2006a). An oral intake test in rats has shown that eriocitrin is absorbed after it is converted to eriodictyol of an aglycone by intestinal bacteria (Miyake et al, 2000). LFA containing 14.7% eriodictyol has been reported to be prepared from LF by β-glucosidase (G4511, from almonds, Sigma Chemical Co., USA) as a reagent, and has been shown to have higher bioavailability than LF in oral ingestion tests in humans (Sakurai, et al, 2003;Miyake et al, 2006b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations